Physical Activity, Obesity Status, and Blood Pressure in Preschool Children. - Vale, S (2015)
OBJECTIVE:To examine the combined effects of physical activity and weight status on blood pressure (BP) in preschool-aged children. STUDY DESIGN: The sample included 733 preschool-aged children (49% female). Physical activity was objectively assessed on 7 consecutive days by accelerometry. Children were categorized as sufficiently active if they met the recommendation of at least 60 minutes daily of moderate-to-vigorous physical activity (MVPA). Body mass index was used to categorize children as nonoverweight or overweight/obese, according to the International Obesity Task Force benchmarks. BP was measured using an automated BP monitor and categorized as elevated or normal using BP percentile-based cut-points for age, sex, and height. RESULTS: The prevalence of elevated systolic BP (SBP) and diastolic BP was 7.7% and 3.0%, respectively. The prevalence of overweight/obese was 32%, and about 15% of children did not accomplish the recommended 60 minutes of daily MVPA. After controlling for age and sex, overweight/obese children who did not meet the daily MVPA recommendation were 3 times more likely (OR 3.8; CI 1.6-8.6) to have elevated SBP than nonoverweight children who met the daily MVPA recommendation. CONCLUSIONS: Overweight or obese preschool-aged children with insufficient levels of MVPA are at significantly greater risk for elevated SBP than their nonoverweight and sufficiently active counterparts.